2019
DOI: 10.1029/2018wr024671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tidally Varying Salinity on Groundwater Flow and Solute Transport: Insights From Modelling an Idealized Creek Marsh Aquifer

Abstract: Most existing numerical research on tide‐induced groundwater dynamics assumes a constant surface water salinity on the seaward boundary (constant salinity case). Few studies have investigated the influence of tidally varying salinity on shallow groundwater dynamics in coastal aquifers (tidal salinity case). We compiled field observations of tidally varying salinity in multiple estuaries across the eastern coast of China and a tidal creek in North Inlet‐Winyah Bay, United States. Numerical simulations were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 81 publications
2
30
0
Order By: Relevance
“…Approaches to evaluate SGD mainly include seepage meters [21][22][23], hydrological models [24][25][26], and geochemical tracers [27,28]. In particular, naturally occurring geochemical tracers, such as radium as radium ( 223,224,226,228 Ra) and radon ( 222 Rn) isotopes, have been widely used in tracing SGD and water mixing processes in coastal systems [14,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to evaluate SGD mainly include seepage meters [21][22][23], hydrological models [24][25][26], and geochemical tracers [27,28]. In particular, naturally occurring geochemical tracers, such as radium as radium ( 223,224,226,228 Ra) and radon ( 222 Rn) isotopes, have been widely used in tracing SGD and water mixing processes in coastal systems [14,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…To understand how soil stratigraphy would affect the variabledensity flow and solute movement in salt marshes, the current study set up Case H without soil stratigraphy and Case L with a mud layer overlying a sand layer. Following Xiao et al (2019a), who established the numerical model based on investigations of the Crabhaul creek in North inlet-Winyah Bay National Estuarine Research Reserve system, Case H considers homogeneous sandy marsh sediments, with the K s and φ set to 1 × 10 −3 m s −1 and 0.36. Case L uses a layered soil structure of a 2-m mud layer overlying a 3-m sand layer, with K s and φ being 1 × 10 −5 m s −1 and 0.65 for mud.…”
Section: Simulation Cases and Parametersmentioning
confidence: 99%
“…The interplay of soil stratigraphy and salinity contrasts has been rarely investigated. One exception is the recent work of Xiao et al (2019a), which examined the combined effects of tidally varying salinity and soil heterogeneity on subsurface hydrology in salt marshes. However, the findings of Xiao et al (2019a) are applicable to micro-tidal marshes only, because they did not consider tidal inundation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SGD‐associated carbon fluxes are found to be significant in regional and global carbon budgets (Cai et al., 2003; Chen & Borges, 2009; Moore, 2010; Moore et al., 2006; Santos et al., 2009), which have great impacts on the carbonate system in coastal ocean (Atkins et al., 2013; Kim et al., 2011; Liu et al., 2012). Previous studies have also demonstrated that SGD provides an important source of nutrients (Moore et al., 2006; Rodellas et al., 2015; Santos et al., 2009; Slomp & Van Cappellen, 2004; Wang et al., 2018, 2020; Zhang, Santos, Li, Wang, Xiao, Guo, & Wang, 2020) and metals (Beck et al., 2007; Bone et al., 2007; Johannesson & Burdige, 2007; Windom et al., 2006) to salt marshes (Cai et al., 2000), estuaries (Moore et al., 2006; Santos et al., 2009), coral reefs (Paytan et al., 2006; Santos et al., 2010), bay systems (Wang et al., 2018, 2020; Zhang, Wang, Li & Song, 2020), and other ecosystems on the continental shelf (Cai et al., 2020; Moore, 2010; Xiao et al., 2019). Therefore, a mechanistic understanding of SGD input is crucial to improve our knowledge on the coastal biogeochemical dynamics.…”
Section: Introductionmentioning
confidence: 99%